Is ride-hailing a valuable means of transport in newly developed areas under TOD-oriented urbanization in China? Evidence from Chengdu City. (October 2021) - Qiao, Si; Yeh, Anthony Gar-On
Abstract: Even researchers have exerted great efforts to explore the complex relationships between urbanization and travel behaviors, the ride-hailing preference in the newly developed areas under transit-oriented development remains unclear. Considering ride-hailing is increasingly popular throughout the world and the travel behavior of urban residents has undergone tremendous changes due to the rapid urbanization process, assessing the use and values of ride-hailing in outlying new areas is worthy of notice. Hence, this study has applied spatial and temporal models to investigate the determinants of ride-hailing usage in the inner city and newly developed areas. By unpacking the differences in ride-hailing behaviors between inner city and newly developed areas, the preference of ride-hailing is associated with differentiation of socio-economic status, which is formed in the context of urbanization. In contrast, street design and destination accessibility on ride-hailing intensity in newly developed neighborhoods and inner-city neighborhoods shows similar effects. Overall, this study verified that the potential values of ride-hailing services in newly developed areas of the city are reflected in two aspects, females travel and night time travel. Thus, ride-hailing embedded into the conceptual framework of Mobility-as-a-Service (MaaS) is expected to promote multimodal travel options in newly developed areas and help to achieve sustainable, fair, and efficient urban development in the future.